2005
DOI: 10.1104/pp.105.062414
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation Phenotypes of Gibberellin and Brassinosteroid Mutants of Pea

Abstract: The initiation and development of legume nodules induced by compatible Rhizobium species requires a complex signal exchange involving both plant and bacterial compounds. Phytohormones have been implicated in this process, although in many cases direct evidence is lacking. Here, we characterize the root and nodulation phenotypes of various mutant lines of pea (Pisum sativum) that display alterations in their phytohormone levels and/or perception. Mutants possessing root systems deficient in gibberellins (GAs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
242
3
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(272 citation statements)
references
References 46 publications
22
242
3
5
Order By: Relevance
“…Pea (Pisum sativum) mutants deficient in BRs or GA had reduced nodulation (Ferguson et al, 2005), and SL levels were positively correlated with nodulation in pea and L. japonicus (Soto et al, 2010;Foo and Davies, 2011;Foo and Reid, 2013;Liu et al, 2013), but infection was not characterized in these studies. Our observation that CCD8 is induced in root hairs by S. meliloti taken together with the identification of SLs in M. truncatula root exudates (Liu et al, 2011) raises the possibility that SLs are secreted during infection.…”
Section: Discussionmentioning
confidence: 72%
“…Pea (Pisum sativum) mutants deficient in BRs or GA had reduced nodulation (Ferguson et al, 2005), and SL levels were positively correlated with nodulation in pea and L. japonicus (Soto et al, 2010;Foo and Davies, 2011;Foo and Reid, 2013;Liu et al, 2013), but infection was not characterized in these studies. Our observation that CCD8 is induced in root hairs by S. meliloti taken together with the identification of SLs in M. truncatula root exudates (Liu et al, 2011) raises the possibility that SLs are secreted during infection.…”
Section: Discussionmentioning
confidence: 72%
“…A significant body of evidence also points to elevated GA levels, as recorded in the HCT down-regulated roots, as a potential cause of hypernodulation. For example, mutations in pea (Pisum sativum) that reduce GA levels strongly inhibit nodule development, and exogenous application of GA rescues the mutant phenotype (Ferguson et al, 2005). Moreover, GA response genes and GA biosynthetic pathway genes are up-regulated after rhizobial infection in Sesbania rostrata and soybean (Lievens et al, 2005;Hayashi et al, 2012), and constitutive GA Figure 7.…”
Section: Discussion Nodulation In Roots Of Reduced-lignin Alfalfa Plantsmentioning
confidence: 99%
“…signaling mutants can also exhibit reduced nodule formation (Ferguson et al, 2011). Interestingly, GA 4 is the main accumulated bioactive GA in HCT downregulated alfalfa roots, compared with GA 1 or GA 3 in pea and Lotus japonicus (Ferguson et al, 2005(Ferguson et al, , 2011Maekawa et al, 2009), although knowledge of the role of this bioactive form in nodulation is limited.…”
Section: Discussion Nodulation In Roots Of Reduced-lignin Alfalfa Plantsmentioning
confidence: 99%
“…Thus, negative regulation of nodulation by BR might be mediated through the action of spermidine in shoots. In spite of the immobility of BR in the pea (Pisum sativum) (Symons and Reid, 2004), defective nodulation in a BRdeficient pea mutant was recovered in wild-type shoot grafting experiments, implying that BRs might regulate shoot-derived AON signaling via unknown pathways (Ferguson et al, 2005). It is clear that BR play a critical role in AON; however, the discrepancy between the negative effects of exogenous BR on nodulation and impaired nodule formation in BR-biosynthetic or BR-insensitive pea mutants suggests that BR might differentially control nodulation with respect to local and systemic regulation.…”
Section: Plant Hormones As Candidates For Shoot-derived Signals In Aonmentioning
confidence: 99%
“…Application of GA biosynthesis inhibitors causes severe nodulation defects in Sesbania (Sesbania rostrata) (Lievens et al, 2005). A GA-deficient pea mutant also showed decreased nodule numbers (Ferguson et al, 2005;Ross et al, 2005). However, recent genetic and pharmacological studies of GA during nodulation have revealed a negative effect of GA on nodule development by L. japonicus.…”
Section: Are Local Inhibitory Hormone Signals Integrated Into Mapk Camentioning
confidence: 99%